Investigation of swelling, drug release and diffusion behaviors of poly(N-isopropylacrylamide)/poly (N-vinylpyrrolidone) full-IPN hydrogels - KAYAMAN APOHAN, NİLHAN (WILEY, 2007)
The synthesis of sequential full interpenetrating polymer networks (IPNs) based on poly (N-isopropylacrylamide) (PNIPAAm) and negatively charged poly(N-vinyl-2-pyrrolidone) (PNVP) was described and their swelling, drug release, and diffusion studies were investigated. PNIPAAm was used as a host network. According to swelling experiments, IPNs gave relatively lower swelling ratios compared to PNIPAAm hydrogel due to the higher cross-linking density. Lidocaine (LD) was used as a model drug for the investigation of drug release behavior of IPNs. LD uptake of the IPNs were found to increase from 24 to 166 (mg LD/g dry gel) with increasing amount of PNIPAAm and AMPS contents in the IPN structure. It was observed that the specific interaction between drug and AMPS co-monomer influenced the drug release profile. In the diffusion transport mechanism study in water, the results indicated that the swelling exponents n for all IPNs are in the range from 0.50 to 0.72. This implies that the swelling transport mechanism was transferred from Fickian to non-Fickian transport, with increasing AMPS content and NIPAAm character in the IPN structure. In addition, diffusion of LD within the IPNs showed similar trend. The incorporation of AMPS leads to an increase in electrostatic interaction between charge sites on carboxylate ions and cationic LD molecules. Therefore, the highest diffusion coefficient (D) of drug was found for IPN2 sample. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: poly(N-isopropylacrylamide); poly(N-vinyl-2-pyrrolidone); IPN; diffusion; drug release; POLY(ITACONIC ACID); PHASE-TRANSITION; SWOLLEN GELS; POLYACRYLAMIDE; POLY(1-VINYL-2-PYRROLIDONE); TEMPERATURE; COPOLYMERS; SOLUTE